2008
DOI: 10.1002/elan.200804260
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxidation of Some Carbohydrates by Nickel/Poly(o‐Aminophenol) Modified Carbon Paste Electrode

Abstract: This study investigates the electrocatalytic oxidation of glucose and some other carbohydrates on nickel/poly(oaminophenol) modified carbon paste electrode as an enzyme free electrode in alkaline solution. Poly(o-aminophenol) was prepared by electropolymerization using a carbon paste electrode bulk modified with o-aminophenol and continuous cyclic voltammetry in HClO 4 solution. Then Ni(II) ions were incorporated to electrode by immersion of the polymeric modified electrode having amine group in 1 M Ni(II) ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 33 publications
(26 reference statements)
0
8
1
Order By: Relevance
“…The detection limit was estimated to be 3.74 μM at a signal-tonoise ratio of 3. As shown in Table 1, the detection potential, linear range, detection limit and sensitivity are lower than that in previous reports [20,[43][44][45][46][47][48][49]. …”
Section: Niooh þ Glucose→niðohþ 2 þ Gluconic Acid ð2þcontrasting
confidence: 78%
“…The detection limit was estimated to be 3.74 μM at a signal-tonoise ratio of 3. As shown in Table 1, the detection potential, linear range, detection limit and sensitivity are lower than that in previous reports [20,[43][44][45][46][47][48][49]. …”
Section: Niooh þ Glucose→niðohþ 2 þ Gluconic Acid ð2þcontrasting
confidence: 78%
“…4A shows the amperometric responses of the NiCFP electrode to successive injection of glucose at low concentrations. As indicated, fast response with 95% of the steady-state current achieved within 5 s could be observed, and the limit of detection was 1 M, which is lower than that obtained at the Ni complex (Ojani et al, 2008), CNT-based composite (Deng et al, 2008;Chen et al, 2008) and alloy modified electrodes . The calibration plot for glucose determination was linear in a wide range from 2 M to 2.5 mM with a slope of 3.3 A mM −1 (sensitivity) and a correlation coefficient of 0.9997 (Fig.…”
Section: Amperometric Determination Of Glucose At Nicfp Electrodementioning
confidence: 71%
“…Among these relatively low-cost catalysts, Ni-based materials were extensively investigated for electrocatalytic oxidation of many important analytes besides carbohydrates (Reim and Effen, 1986;Casella and Gatta, 2001;You et al, 2003;Ojani et al, 2008), such as insulin (Salimi et al, 2007), aspirin (McAuley and Wildgoose, 2008), ethanol (Casella et al, 1993;Weng et al, 2004) and amino acids (Deo et al, 2004). The oxidation processes are catalyzed by the Ni-based materials through the formation of a high-valent, oxyhydroxide species (NiOOH) in alkaline medium.…”
Section: Introductionmentioning
confidence: 99%
“…Differential pulse voltammograms obtained with increasing amounts of CPM showed that the peak current increased linearly with increasing concentration, as shown in Figure. 6. Using the optimum conditions described previously, linear calibration curves were obtained for CPM in the range of 8.0 10 À6 to 1.0 10 À4 M (Figure 6 Inset) [24]. The linear equation was I p = 4.7133 + 1.868 (r = 0.9891, C is in mM).…”
Section: Calibration Curvementioning
confidence: 99%